Instructional Scaffolding to Improve Students’ Learning Outcome and Activeness - Oktalia, Dwi; Radiatan, Mardiah; Ansyah, Hary (English Education : English Journal for Teaching and Learning, 2023)
Activeness and low learning outcomes are some problems that may be faced by the teachers during the implementation of the curriculum Merdeka. These two problems may be affected by students' backgrounds and characteristics. In order to help students get better learning experiences and improve their learning outcomes, teachers may use instructional scaffolding. This study is a classroom action research. The data were collected by using observation and analyzing students' learning outcomes. The research participants are students in class 7 at a middle school in Jambi province. The result shows that there is improvement in students' activeness in answering teachers' questions and task submission, besides there is also improvement in students' learning outcomes although some of the students did not show any significant improvement.